DEVELOPMENT OF COMPLEX PROBLEM SOLVING TESTS IN NEWTON’S DYNAMIC FOR HIGH SCHOOL - Nurhikmah Weisdiyanti; Sahyar Sahyar; Rita Juliani (Universitas Negeri Medan, 2023)
Complex problem solving (CPS) is important for students, but educators rarely provide tests that hone CPS, because the available tests are not up to standard. The aim of the study was to develop a physics test instrument based on CPS for high school that met the qualifications in the aspects of validity, reliability, discriminatory power and level of difficulty. The type of research used is the Borg & Gall research and development (R&D) model with 9 stages, namely: (1) preliminary study of problem-solving test instruments, (2) planning of instrument development and testing, (3) development of problem-solving-based test instruments, (4) initial field test by 5 material, construction and language expert validators, (5) main product revision, (6) main field test on 20 test takers, (7) operational product revision, (8) operational field test on 100 participants tests, and (9) final product revisions. This research uses a mixed method approach with qualitative and quantitative analysis. The developed test instrument consists of 15 essay test items. The results of the initial field test obtained 30 valid test items with minor revisions on the material, construction and language aspects. The results of the main field test obtained 14 test items valid and very reliable. The operational field test results obtained 14 valid and very reliable test items so that the CPS test is suitable for use and can be useful in helping educators to hone students' CPS ability.